Effect of Genotype on Growth and Basic Carcass Characteristics in Male Lambs - Svatava Koutná; Jan Kuchtík; Radek Filipčík (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2016)
The aim of the study was to evaluate the effect of a genotype on growth and basic carcass characteristics in male lambs. The experiment was carried out at an organic farm in Proseč and four different genotypes were included in the experiment: Šumavská sheep (S) 100, n = 8; S 50 Texel (T) 50, n = 11; T 75 S 25, n = 13 and S 75 T 25, n = 11. The genotype had no significant effect on most of the monitored growth parameters. The highest daily gain (DG) in the interval from birth to 100 days of age was found out in S 75 T 25 (327 g) but the highest DG from birth until the end of the experiment was found in S 50 T 50 (199 g). By contrast, the lowest DGs in both above mentioned intervals were found out in S 100 (265 and 147 g, respectively). With regards to basic carcass characteristics, the genotype had a significant effect only on proportion of kidney. The highest carcass yield (44.80%) was found in S 50 T 50 and the lowest (37.66%) in S 100. The best conformation score was found in S 75 T 25 (3.18) and the lowest fatness score in S 50 T 50. To conclude, it is possible to state that use of the Texel rams in crossing with the Šumavská ewes had a positive effect on both growth and basic carcass characteristics.